- James Zediana
- Haverhill, MA
- United States

This conversation is closed.

## Where did we come from?

I started several debates in TED and results are evolution can't be proven. SHORT OF CREATION and EVOLUTION is there another option?

I believe this is a fundamental question to be answered.

**Topics:**creation evolution intelligent design

**Showing single comment thread. View the full conversation.**

**Showing single comment thread.
View the full conversation.**

## Barry Palmer 100+

Check out this essay.

http://chem.tufts.edu/answersinscience/relativityofwrong.htm

## daniel hehir 20+

I read the essay but wasn't too impressed. It seems to promote a form of relativism that in my mind is a hinder to the true understanding of the nature of thinking.

You might also consider this.

1 is the largest number. All other numbers are divisible. While 1 can only be divided by itself.

In mathematics as well as geometry things can in fact be proven. In as much as we consider our own thoughts as "real"...... then we have to come to the conclusion that mathematical and geometrical truths as real and are also proven correct or incorrect. If one chooses to deny this, then you at the same time deny the entire foundation of science.

If then real truth can be achieved through mathematics and geometry, then the "ideas" must also be fully real in themselves... or ? Is not mathematics existing only purely in the ideal realm ...?

As we now stand in the danger of wandering further and further away from James's initial question, "Where do we come from?" The fact that we are here presented with an "immaterial" truth that is quite real.

If we can consider this immaterial truth as being founded "in reality" then why should we not consider other immaterial truths to also be just as much founded in the same reality.

## James Zediana

or

a = 1

b = 1

a = b

a2 = b2

a2 - b2 = 0

(a-b)(a+b) = 0

(a-b)(a+b)/(a-b) = 0/(a-b)

1(a+b) = 0

(a+b) = 0

1 + 1 = 0

2 = 0

1 = 0

1 + 1 = 1

## Fritzie - 200+

## Obey No1kinobe 100+

to 1(a+b) = 0

Anyway (a-b)(a+b)/(a-b) = 0/(a-b)

= (0)(2)/(0) = 0/(0)

even if you multiply both sides by (a-b) you get

(a-b)(a-b)(a+b)/(a-b) = (a-b) 0/(a-b)

=> (0)(0)(2)/(0) = (0)0/0

## James Zediana